Peningkatan kapasitas pengelola Unit Farming Club melalui pelatihan budidaya maggot black soldier fly - Sukmawati, Sri; Kasim, Niken Nur; Wiridannissaa, Nurul; Nasrul, Muh.; Ilham, Ilham; Zainuddin, Dian Utami; Purnama, Dirhana; Mahendra, Yusril (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
The Farming Club Unit (UFC) is a student organization that focuses on sustainable agriculture through hydroponic cultivation. However, limited business diversification has hindered its economic potential, necessitating innovations to strengthen the institution and increase revenue. One promising solution is the farming of Black Soldier Fly (BSF) maggots as an alternative for organic waste management and sustainable animal feed production. This community service program was implemented using a participatory-educational approach, which included lectures, interactive discussions, BSF farming demonstrations, and independent maintenance practices conducted by participants under the guidance of the service team. Evaluation was conducted using pre-test and post-test instruments, analyzed descriptively, and supported by gain score calculation to measure program effectiveness. The results revealed a significant improvement in participants' knowledge, from an average pre-test score of 31.0% to a post-test score of 95.3%, with an average gain score of 0.92 (in the high category). These findings indicate that the training effectively enhanced the capacity of UFC managers in mastering BSF maggot farming skills. The implication of this program is the creation of opportunities for UFC to diversify its business, generate additional income, and contribute to reducing organic waste generation through sustainable agricultural practices.